Paralogism in Abul Ala Mawdudi's Khilafat wa Mulukiyat: A Critical Analysis of Taqi Usmani's Refutation - Atif Suhail Siddiqui (Surau Journal of Islamic Studies, 2026)
This study critically examines the presence of paralogism in Abul Ala Mawdudi’s Khilafat wa Mulukiyat through an analysis of Taqi Usmani’s systematic refutation. While Khilafat wa Mulukiyat has significantly influenced modern Islamic political thought, its historiographical methodology remains highly contested among Sunni scholars, particularly regarding its interpretation of the early caliphate and the Companions of the Prophet. Employing a qualitative textual analysis, this study compares Mawdudi’s historical arguments with classical Islamic sources and Usmani’s methodological critique. The analysis identifies recurring forms of paralogism, including selective use of historical evidence, omission of contradictory reports, conflation of legitimate ijtihad with bid’ah, and contextual misinterpretation of key narrations concerning Muawiyah ibn Abi Sufyan. These argumentative patterns are contrasted with Usmani’s emphasis on source verification, the methodological principles of al-jarh wa al-ta’dil, and the ethical norms governing Islamic historiography. The study argues that the debate extends beyond historical disagreement to competing epistemological approaches for evaluating Islamic history and religious authority. It contributes to contemporary scholarship by demonstrating how methodological rigor and critical source evaluation remain essential for interpreting contested narratives within Islamic intellectual history.